Effects of robotic-assistance gait training in adults stroke (Research, Society and Development, 2022)
Objective: To identify the effects generated by gait training with robotic assistance in post-stroke patients. Materials and methods: In order to achieve the proposed objective, a described and exploratory study of na Integrative Literature Review (ILR) was carried out. In order to develop the guiding question of this RIL, the domains of the PICO strategy were applied. The question at hand: “What are the effects of robotic-assisted gait training in post-stroke adults?” A bibliographic survey was carried out in October 2022 in the following databases: Embase via Cochrane Library, LILACS via VHL and MEDLINE via PubMed. The search strategies were formulated from the mentioned descriptors in Portuguese and English, linked by the Boolean operator “AND”. Results: 14 scientific articles were selected to compose the final sample of the RIL. Discussion: With the use of robotic assistance, the equipment facilitates the symmetrical pattern, corresponding to the normal kinematics of the gait, providing important afferent tips for the rehabilitation process, minimizing vices and promoting substantial enthusiasm to optimize and increase the functional gain of gait, in addition to minimize the therapist’s effort. Final considerations: Therefore, most of the scientific evidence from the study showed that gait training with robotic assistance generates significant effects in post-stroke patients, among them, improvements in static and dynamic balance, lower limb functionality, speed, stride length, cadence and spatio-temporal parameters of gait.